Ganglioside GD3 synthase (GD3S), a novel cancer drug target - Liu, Jinyi (Acta Pharm Sin B, 2018)
Gangliosides are a class of important glycosphingolipids containing sialic acid that are widely distributed on the outer surface of cells and are abundantly distributed in brain tissue. Disialoganglioside with three glycosyl groups (GD3) and disialoganglioside with two glycosyl groups (GD2) are markedly increased in pathological conditions such as cancers and neurodegenerative diseases. GD3 and GD2 were found to play important roles in cancers by mediating cell proliferation, migration, invasion, adhesion, angiogenesis and in preventing immunosuppression of tumors. GD3 synthase (GD3S) is the regulatory enzyme of GD3 and GD2 synthesis, and is important in tumorigenesis and the development of cancers. The study of GD3S as a drug target may be of great significance for the discovery of new drugs for cancer treatment. This review will describe the gangliosides and their roles in physiological and pathological conditions; the roles of GD3 and GD2 in cancers; the expression, functions and mechanisms of GD3S, and its potential as a drug target in cancers.